Accidental Poisoning of a Child by Dieffenbachia - Emel Ataş Berksoy; Ebru Topalakçı; Özlem Bekem Soylu; Tanju Çelik (Galenos Yayinevi, 2018)
Dieffenbachia is a tropical ornamental house plant. Accidental ingestion of the leaf or its seed can cause serious gastrointestinal and respiratory symptoms requiring emergency treatment. An eight-year-female child was admitted to the emergency department with sudden numbness on her tongue, lower lip swelling and redness, slurred speech and difficulty breathing. Upon further interview, it was revealed that five minutes prior to these symptoms occurred, the patient was playing with the soil of dieffenbachia with a pen and placing this pen in her mouth. Symptoms resolved after treatment with antihistamines and steroids. Training of families and children about toxic effects of Dieffenbachia which is widely used as a potted house plant is very important as chewing the plant results in life-threatening consequences.